2019
DOI: 10.3221/igf-esis.48.69
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue reliability assessment of small sample excavator working devices based on Bootstrap method

Abstract: To evaluate the fatigue reliability of the excavator working device, the fatigue tests of 2 sets of moving arm and bucket rod of medium-sized excavators with self-weight of 26000 kgwere carried out. The virtual augmented sample method (VASM) combined with Bootstrap method was used to analyze the reliability of the excavator working device under extreme small samples, and the interval and point estimations of life parameters were obtained. Based on the lognormal distribution of the excavator working device, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The strain energy density-fatigue life (W t -N f ) curve can be solved using a two-parameter power function model [43] as shown in Equation ( 7) or a three-parameter power function model [44] as shown in Equation (8). Formally, the three-parameter model has one more constant term than the two-parameter model, which can express the endurance limit of the model curve.…”
Section: W T -N F Curve and P-w T -N F Curve Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain energy density-fatigue life (W t -N f ) curve can be solved using a two-parameter power function model [43] as shown in Equation ( 7) or a three-parameter power function model [44] as shown in Equation (8). Formally, the three-parameter model has one more constant term than the two-parameter model, which can express the endurance limit of the model curve.…”
Section: W T -N F Curve and P-w T -N F Curve Calculation Methodsmentioning
confidence: 99%
“…Solving fatigue damage problems in engineering structures requires fatigue test data to obtain large samples of data. It has been found that even if the fatigue test is conducted under the same conditions, the fatigue life obtained from the same material specimens has deviations, and the fatigue life has an unavoidable discrete nature [ 8 , 9 , 10 ]. The fatigue test has the features of a long cycle time and high cost; it is difficult to obtain large sample data that meet the requirements of traditional statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…It not only bears its own weight but also effectively handles dynamic loads from excavation activities. Additionally, it is highly prone to fatigue fractures [ [5] , [6] , [7] , [8] ].However, the harsh operating environment and fluctuating loads can cause stress changes, potentially leading to fatigue failure [ [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have developed different sampling methods for complex problems. For instance, Yang proposed an improved bootstrap method based on gray theory, 27 James introduced several new variants of the wild cluster bootstrap, 28 Shao improved bootstrap by using the virtual augmented sample method to analyze reliability, 29 and Chang proposed a parametric bootstrap approach to improve the Durbin‐Watson test, which is inaccurate for small samples 30 . The bootstrap method has been widely applied in various fields, such as medicine, 31 biology, 32 mechanical engineering, 33 aerospace, 34 and so forth.…”
Section: Introductionmentioning
confidence: 99%